THE IMPACT OF PROMOTIONAL ACTIVITIES ON PURCHASE DECISION MAKING: â€œA CASE STUDY OF BRANDS BONITA AND RUGOVE -WATER BOTTLED PRODUCERSâ€ - Ismajli, Ali; Kajtazi, Saranda; Fejza, Ejup (European Scientific Journal, ESJ, 2013)
Marketing is a very important aspect of business, because it contributes to a large extent to the overall success of the organization, thus production and distribution depends exactly on it. Promotional activities and other relevant factor of purchasing decision making attracts customers to at least try the product, and then decide if the quality meet the necessary requirements of their needs and demands. This paper addresses the aspect of promotion strategies and the activities of bottled water with the aim of keeping existing customers and attracting new ones. The purpose of this paper is to analyze the impact of promotional activities during the decision making process and the buying behavior of bottled water, which is focused basically on two major producers of bottled water in Kosovo. These producers are company BONUS from Prishtina with bottled water brand BONITA and company UNIOR Aqua, which is a branch of UNIOR from Slovenia, producing bottled water in Kosovo with brand RUGOVE. Both companies produce different types of bottled water in PET and glass packaging and are very committed to meeting the needs of the market, and are also committed to the trend of introducing new products or improving existing ones towards the market needs. For the purpose of this paper, we conducted a research through questionnaires. Questionnaires were distributed directly and through the use of email to the end users. 200 questionnaires were distributed for this purpose and feedback was gotten on 150 questionnaires. Target groups selected for interview were of different ages and different professions. Limitations were made only on age and for the purpose of this research, the age under 18 years were excluded. Research was conducted in the main cities of Kosovo and was done in the period between the month of April and June 2013.